Exploring the associative learning capabilities of the segmented attractor network for lifelong learning - Jones, Alexander; Jha, Rashmi (Frontiers in Artificial Intelligence, 2022)
This work explores the process of adapting the segmented attractor network to a lifelong learning setting. Taking inspirations from Hopfield networks and content-addressable memory, the segmented attractor network is a powerful tool for associative memory applications. The network’s performance as an associative memory is analyzed using multiple metrics. In addition to the network’s general hit rate, its capability to recall unique memories and their frequency is also evaluated with respect to time. Finally, additional learning techniques are implemented to enhance the network’s recall capacity in the application of lifelong learning. These learning techniques are based on human cognitive functions such as memory consolidation, prediction, and forgetting.